KONTRIBUSI WORK ENVIRONMENT DAN JOB SATISFACTION SEBAGAI MULTI MEDIASI TERHADAP JOB PERFORMANCE - Rina Hartanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
The purpose of this study is to analyze the impact of emotional leadership competency on employees’ job performance through work environment and job satisfaction. In addition, this study also analyzes the effect of emotional leadership competency, work environment, job satisfaction dimensions on employees job performance. The samples are obtained by distributing 300 questionnaires to all HRD Manager (Human Resource Manager) respectively to travel agencies in five areas in Jakarta who then distribute the questionnaires to front line employees as the respondents of the 300 questionnaires distributed, only 261 questionnaires were successfully retrieved from the HRD Manager and analyzed by using Structural Equation Models (SEM). The results showed that 1) emotional leadership competency does not directly affect employees’ performance, but emotional leadership competency mediated by work environment and job satisfaction positively and significantly affects the performance of travel agency employees, 2) emotional leadership competency positevely and significantly affects work environment, 3) emotional leadership competency does not affect employees’ performance, 4) work environment positevely and significantly affects employees’ job satisfaction, and 5) job satisfaction positively and significantly affects employees’ performance.